ANALISIS WAKTU PENYINARAN PADA KALIBRASI DOSIMETER SAKU GAMMA (PEN DOSIMETER) - Herianti, Herianti; Sahara, Sahara; Hernawati, Hernawati (JFT : Jurnal Fisika dan Terapannya, 2015)
The Purpose of this research is to know the effects of time irradiation to dosage in calibration dosimeter pocket gamma (pen dosimeter).  This research is also intended to know the effects of time irradiation in response dosimeter pocket gamma (pen dosimeter).  Relations between time irradiation to dosage based on calculations time irradiation, irradiation in pen dosimeter to calculate dosage reading material. Result of contact time irradiation with the dose by more than dosage that used time irradiation needed more for a long time. Results obtained from the relationship time irradiation in response dosage is becoming more time irradiation then dosage that read in pen dosimeter result in more than. dosage 100 µSv, 500 µSv, 1000 µSv, 1500 µSv, 2000 µSv, 2500 µSv, 3000 µSv, 3500 µSv, 4000 µSv, and 4,500 µSv, factors calibration 0.91 . Calibration factor which is obtained from pen dosimeter that has been calibration claimed could be used and functioned as specifications based on standard calibration.